Furan resin as a replacement of phenolics: influence of the clay addition on its thermal degradation and fire behaviour - Rivero, Guadalupe (2014)
Nanocomposites based on a furan resin and different types of clays were obtained. Their thermal and fire behaviours were compared with traditional phenolic resins, which are known by their excellent flame resistance. Three types of montmorillonite clays were in situ added to the thermosetting matrix. A cone calorimeter and a smoke chamber were used to evaluate the performance of the materials against fire and their smokes generation. Global parameters were calculated for comparison purposes. Fires derived from the furan resin combustion grow faster than the phenolic ones, but they are extinguished more rapidly. This effect is enhanced by the incorporation of inorganic nanofillers. The only addition of any clay causes shorter fires but slightly speeds up the degradation process. A homogeneous nanofiller dispersion was found to be crucial to achieve good fire behaviour. Nevertheless, formaterials with similar dispersion, the crosslinking degree of the polymer matrix appears as a secondary factor that determines slighter differences in the performance. Nanocomposites with organomodified clays showed a quite similar fire performance, though the composite containing the clay (Southern Clay Products, Inc., Louisville, Ky, USA) Cloisite®30B showed the best performance taking into account both the fire risk and the smoke evolution and obscuration.